2021
DOI: 10.5209/rced.70173
|View full text |Cite
|
Sign up to set email alerts
|

El feedback entre iguales y su incidencia en el desarrollo profesional docente

Abstract: Este artículo presenta los resultados de una investigación sobre la implementación de un Programa de Observación y feedback entre iguales (POFEI) en 47 centros escolares de la comunidad de XX. Se trata de una experiencia pionera, auspiciada por la XX, que trata de valorar de qué modo el POFEI contribuye al desarrollo de la práctica profesional. En concreto, el trabajo se centra en identificar, caracterizar y valorar el feedback que surge entre las parejas docentes que participan en el programa. Para ello se ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
1
9
0
3
Order By: Relevance
“…When there is a lack of trust, peer feedback can entail high levels of anxiety, as the view of others influences the construction of one's own self‐image and identity as a teacher (Castañeda‐Londoño, 2017). Moreover, research has consistently shown that teachers perceive a lack of skills in giving and receiving constructive, non‐judgmental feedback (Corcelles‐Seuba, Soler, et al., 2023; Carroll & O'Loughlin, 2014; Rosselló & De la Iglesia, 2021). Excessive criticism focused only on negative comments or a lack of sensitivity in giving feedback can be perceived as discouraging and generate negative feelings, which may increase teachers' resistance to RPO (Nguyen & Pham, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When there is a lack of trust, peer feedback can entail high levels of anxiety, as the view of others influences the construction of one's own self‐image and identity as a teacher (Castañeda‐Londoño, 2017). Moreover, research has consistently shown that teachers perceive a lack of skills in giving and receiving constructive, non‐judgmental feedback (Corcelles‐Seuba, Soler, et al., 2023; Carroll & O'Loughlin, 2014; Rosselló & De la Iglesia, 2021). Excessive criticism focused only on negative comments or a lack of sensitivity in giving feedback can be perceived as discouraging and generate negative feelings, which may increase teachers' resistance to RPO (Nguyen & Pham, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Time constraints have been widely reported to hinder RPO and increase teachers' resistance to it (Corcelles-Seuba, Soler, et al, 2023;Golden et al, 2021;Nguyen & Pham, 2020;Rosselló & De la Iglesia, 2021;Verástegui & González, 2019). Institutional support is needed to provide time for teachers to coordinate and complete the three stages of the process within teachers' working hours.…”
Section: Introductionmentioning
confidence: 99%
“…As stated in a recent study [4]: "when peer observation of teaching is incorporated into the practice and culture of the university and it is carried out in a mutually respectful and supportive way, it has the potential to facilitate a reflective change and teacher growth." This also means that peer feedback is a powerful tool that can be used to strengthen professional development and improve teaching practices [63], and which also reveals an improvement in trust in collaborative settings [64].…”
Section: Discussionmentioning
confidence: 99%
“…Con respecto al tercer objetivo, se puede concluir que la formación en centro de las maestras del SAEHD contribuye a romper con el aislamiento y soledad que viven. Ellas trabajan en un auténtico entorno colaborativo, donde surge el apoyo mutuo, las responsabilidades compartidas y la reflexión sistemática (Krichesky y Murillo, 2018;Rosselló y De la Iglesia, 2021). Las maestras cuentan con acompañamiento a través de los procesos de asesoramiento y Volumen 53 número 1, enero-marzo, 2024 / págs.…”
Section: Discusión Y Conclusionesunclassified